A CONFIANÇA E AS CARÊNCIAS DOS GESTORES DO SETOR VAREJISTA DE SANTA ROSA - WAGNER, ADRIANO; SPAREMBERGER, ARIOSTO; ZAMBERLAN, LUCIANO; ZAMIN, MARCIELA; BÜTTENBENDER, PEDRO L.; KÖHLER, ROMUALDO (Salão do Conhecimento, 2013)
Resumo